Pengaruh Pemberian Reward Terhadap Motivasi Belajar Peserta Didik - Meriyani (Metanoia, 2020)
Less effective teaching and learning activities are caused by low student motivation. The purpose of this study was to determine the effect of rewarding on students' learning motivation. The research method used is quantitative method with one shot-case studydesign. The study population in class VII, VIII, IX number of each class 10 people. Data collection techniques using questionnaires and documentation. Data analysis techniques using descriptive data, normality test and simple linear regression test. Based on the results of calculations using the SPSS 16.0 reward variable has a Significance value of 0,000. The results obtained significance value of 0.000 <0.05, it can be concluded that "The Effect of Rewarding on Student Learning Motivation"